Exploring the Structural Diversity and Biotechnological Potential of the Rhodophyte Phycolectome - Éllen F. Rodrigues; Flavia Alves Verza; Felipe Garcia Nishimura; Renê Oliveira Beleboni; Cedric Hermans; Kaat Janssens; Maarten Lieven De Mol; Paco Hulpiau; Mozart Marins (Marine Drugs)
Lectins are non-covalent glycan-binding proteins found in all living organisms, binding specifically to carbohydrates through glycan-binding domains. Lectins have various biological functions, including cell signaling, molecular recognition, and innate immune responses, which play multiple roles in the physiological and developmental processes of organisms. Moreover, their diversity enables biotechnological exploration as biomarkers, biosensors, drug-delivery platforms, and lead molecules for anticancer, antidiabetic, and antimicrobial drugs. Lectins from Rhodophytes (red seaweed) have been extensively reported and characterized for their unique molecular structures, carbohydrate-binding specificities, and important biological activities. The increasing number of sequenced Rhodophyte genomes offers the opportunity to further study this rich source of lectins, potentially uncovering new ones with properties significantly different from their terrestrial plant counterparts, thus opening new biotechnological applications. We compiled literature data and conducted an in-depth analysis of the phycolectomes from all Rhodophyta genomes available in NCBI datasets. Using Hidden Markov Models capable of identifying lectin-type domains, we found at least six different types of lectin domains present in Rhodophytes, demonstrating their potential in identifying new lectins. This review integrates a computational analysis of the Rhodophyte phycolectome with existing information on red algae lectins and their biotechnological potential.